Color and texture of surimi‐like gels made of protein isolate extracted from catfish byproducts are improved by washing and adding soy whey. Issue 7 (16th June 2022) - Zhang, Yan; Chang, Sam K. C.
Abstract : Abstract: Protein extraction from catfish byproducts has been proven economically and technically feasible. However, the gel prepared from protein isolate was dark and lacked elasticity. Byproduct mince washing and application of soy whey were adopted in this study to address the above gel quality issues. Heating soy whey at 75°C for 3 min could eliminate over 99.9% lipoxygenase activity and retain more than 50% trypsin inhibitor activity. Washing byproduct mince for 2 min with water‐to‐mince ratio of 2:1 could achieve satisfactory gel color, which was comparable to that of commercial surimi gels. When soy whey was applied, the autolytic enzyme‐induced proteolysis was inhibited in a dose‐dependent manner by up to 74%. With addition of soy whey, resilience, hardness at maximum force, hardness at 5 mm compression, springiness, cohesiveness, chewiness, fracturability, and deformation could be increased by up to 43.10%, 66.92%, 36.72%, 14.59%, 29.17%, 143.25%, 93.82%, and 27.97%, respectively. However, the texture was still inferior to the gel made from fillet mince. SDS‐PAGE revealed that myosin was most susceptible to proteolysis and application of soy whey could effectively protect it from degradation. Different from tropomyosin, myosin and actin were greatly involved in disulfide bond formation. Practical Application: Catfish byproducts and soy whey, a byproduct from soy protein isolation, are normally treated as waste. The current study proved the possibility to utilize these two byproducts to make value‐added surimi‐like gel products. Utilization of byproducts would not only increase profitability of catfish and soy processing, but also preserve the precious fish proteins and other health‐promoting components.